Effect of Yara Mila Pearl NPK Fertilizer and Nasa Liquid Organic Fertilizer on Growth and Yield of Beans (Phaseolus vulgaris L.) - Muthalib, Abdul; Jannah, Noor (Universitas 17 Agustus 1945 Samarinda, 2018)
The objective the research was to study the effect of NPK Mutiara YaraMila fertilizer and Nasa foliar fertilizeras well as their interaction on the growth and yield of stringbean, and to find proper dosage of NPK Mutiara YaraMila fertilizer and concentration of Nasa foliar fertilizer for optimal yield of stringbean.The research was conducted in the village of Rantau Panjang, sub district of Telen of East Kutai Regency. It carried out from March until June 2016. It applied Completely Randomized Block Design with factorial experiment 4 x 4 and three replications. The first factor was the dose of NPK Mutiara YaraMilafertilizer (P) consists of 4 levels, namely: no NPK Mutiara YaraMilafertilizer (p0), 100 kg ha⁻¹ equals to 25,6 g plot-1 (p1), 200 kg ha⁻¹ equals to 51,20 g plot-1(p2), and 300 kg ha⁻¹ equals to 76,80 g plot-1 (p3). The second factor was the concentration of Nasa foliar fertilizer (B) consists of 4 levels, namely: no Nasa foliar fertilizer (b0), 2 ml l-1 water (b1), 4 ml l-1 water (b2), and ), 6 ml l-1 water (b3).Result of the research revealed that : (1) the NPK Mutiara YaraMila fertilizer treatment affected very significantly on the plant lenght at 10, 20, and 30 days after planting, days of plant flowered, days of plant harvest, number of pods, weight of pods, and production of pods; (2) the Nasa foliar fertilizer was affected significantly to very significantly on thethe plant lenght at 10, 20, and 30 days after planting, days of plant flowered, days of plant harvest, number of pods, weight of pods, and production of pods; (3) interaction between NPK Mutiara YaraMila fertilizer and Nasa foliar fertilizer was affected significantly to very significantly on the plant lenght at 10 and 20 days after planting, days of plant flowered, but no significantly on the plant lenght at 30 days after planting, days of plant harvest, number of pods, weight of pods, and production of pods; (4) the highest pods production is attained by the 300 kg ha-1 NPK Mutiara YaraMila fertilizer (p3), namely 38,38 Mg ha-1 or by the 6 ml l-1 water Nasa foliar fertilizer (b3), namely 38,55 Mg ha ̵ ¹.